Exposition of the Different Schema Clustering (Information Integration) Techniques - Gabison, Gregg Victor D. (JPAIR Multidisciplinary Research, 2009)
The Internet today has provided more opportunities for entities to communicate, exchange information in a very dynamic manner. Explicitly, Web 2.0 and SaaS have provided new kinds of platform/ services which resulted to more web applications taking advantage of the universality of XML. Techniques regarding XML clustering between different heterogenous sources especially in a more open environment are becoming more necessary, which leads to a more efficient handling of the increasing volumes of XML schemas employed. Various (XML clustering) techniques are out in the open, and can be integrated for use in the different application areas, such as E-commerce, data warehousing, unique user supplied query parameters and possibly in any general data integration activity. In this paper, in each of the XML clustering technique, the researcher provides a general idea and its specific approach/ technique with relevance to an intended implementation. Following the approach/ technique will be the presentation of its key advantages and disadvantages.
Keywords: Exposition; schema clustering; information-integration